Development of padlet website learning media based on East Java local wisdom for storytelling skills - Widyaningrum, Heny Kusuma; Hasanudin, Cahyo (Universitas Ahmad Dahlan, 2025)
A This study aims to develop learning media based on the Padlet website to improve storytelling skills among elementary school students through the integration of East Javanese local wisdom. The developed media includes eight main menus, namely the main page, identity profile, learning outcomes, student attendance, material, student worksheet, evaluation, and bibliography, which provide an interactive and engaging learning experience. The research employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) and involved 80 third-grade students as participants. Data were obtained from media and material expert validation questionnaires, as well as student response questionnaires after the implementation stage. The validation results showed that the developed media achieved a validity score of 90% from material experts and 87% from media experts, indicating that the product met the feasibility standards. Moreover, the student response test revealed a very positive perception, particularly in terms of attractiveness, interactivity, and usefulness for learning storytelling skills. These findings demonstrate that the Padlet-based learning media incorporating East Javanese local wisdom is effective, practical, and of high quality in supporting the development of students’ storytelling skills. The significance of this study lies in offering a digital learning innovation that strengthens cultural values while enhancing literacy competence in elementary education.